The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/02726351.2016.1194351
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of fine coal beneficiation by hydrocyclone and multi-gravity separation to produce fine lignite clean coal

Abstract: We evaluated the suitability, contribution to the national economy, and environmental impact of hydrocyclone and Multi-Gravity Separation (MGS) processes using fine-sized coal taken from Downloaded by [The University Of Melbourne Libraries] at 22:43 22 June 2016 2 the Soma coal sludge pond. The lignite coal tailings were treated by a two-stage concentration scheme for the recovery of fine clean coal. Pre-enrichment experiment parameters were determined by Taguchi experimental design method, and the results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…While the drum is rotating, the centrifugal force from drum rotation affects gravity separation so that coarse particles or high density, high ash content, are spiraled outside and settled on drum surface then slowly swiped up by scrapers to be discharged at the outer end. Meanwhile, the fine or light density particles less affected by centrifugal force, form a flowing film above the heavier seam then is conveyed by the shaking of the drum and continually washing water flow to the lower tilt inner end [ [273] , [274] , [275] ]. MGS was applied for the treatment of ultrafine coal as well as tailing pond deposits [ 276 , 277 ].…”
Section: Enhanced Gravity Separation Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the drum is rotating, the centrifugal force from drum rotation affects gravity separation so that coarse particles or high density, high ash content, are spiraled outside and settled on drum surface then slowly swiped up by scrapers to be discharged at the outer end. Meanwhile, the fine or light density particles less affected by centrifugal force, form a flowing film above the heavier seam then is conveyed by the shaking of the drum and continually washing water flow to the lower tilt inner end [ [273] , [274] , [275] ]. MGS was applied for the treatment of ultrafine coal as well as tailing pond deposits [ 276 , 277 ].…”
Section: Enhanced Gravity Separation Technologiesmentioning
confidence: 99%
“…The result showed that drum inclination was determined as a major available on the reduction of ash content and other minor parameters are solid concentration, drum rotation speed, shaking amplitude, wash water rate, and feed rate [ 274 ]. Also, Özbakir et al (2017) proposed a regression model with flow independent inputs (i.e., drum rotation speed, wash water rate, drum inclination, and solid concentration) and two dependent outputs (i.e., ash content and coal yield) variables [ 275 ]. The results showed that ash content and the yield were decreased when lower water flow rate, higher drum rotation speed, higher drum inclination, and solid concentration were used [ 275 ].…”
Section: Enhanced Gravity Separation Technologiesmentioning
confidence: 99%
“…As a result, they managed to reduce the ash content from 30.4% to 12%. Özbakir et al (2017) used a combined optimization of hydrocyclone and multi-gravity separation device to remove ash and sulfur from the coal preparation plant tailings [17]. As a result, they managed to reduce the ash content from 54.82% to 24.52%.…”
Section: Introductionmentioning
confidence: 99%
“…In order to fully present the capability of the device, the working model needs to be developed. A significant part of the research focused on developing models, be that based on statistical correlations, aerodynamic equations, or computational fluid dynamics (CFD) methods, to fully address the problem of process optimisation and to assess achievable effectiveness of the proposed solutions [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%